Improving Mathematical Connection Capability and Learning Outcomes Through Problem-Based Learning Model - Yoga Marga Mahendra; Husamah Husamah; Budiono Budiono (AlphaMath : Journal of Mathematics Education, 2023)
This research is motivated by the low ability of students' mathematical connections and student learning outcomes in learning mathematics in grade IV of elementary school. Based on these problems, this study aims to improve mathematical connection skills and student learning outcomes through problem-based learning models in class IV mathematics learning whole numbers. The research subjects were fourth-grade students at SDN Mojorejo 1 Kota Batu. Data collection is done by testing and documentation. This research uses descriptive quantitative and qualitative analysis with the type of PTK research (classroom action research) by adapting the Kemmis and Taggart models which consist of four stages of planning namely, action, observation, and reflection carried out in two cycles. The results showed that the minimum mixed value of students in the pre-cycle obtained a result of 10%, then increased by 40% in cycle I, students' mathematical connection ability was 50% then increased by 39% to 89% in cycle II. In addition, the results of the average score, namely in the pre-cycle of students' mathematical connection ability, namely 45% then increased by 24% to 69% in cycle I then increased again by 19% to 80%. This shows that there is an increase in the ability of mathematical connections and student learning outcomes after learning using the problem-based learning (PBL) model.